ANALISIS PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PADA KANTOR CAMAT LAHOMI KABUPATEN NIAS BARAT - Gulo, Piardin (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this research is to explain and identify the analysis of training and human resource development needs at the Lahomi District Head Office, West Nias Regency, explain the methods used in training and development, explain the benefits obtained from training and development, explain the supporting factors and inhibiting factors in training and development. development, along with methods for evaluating training and human resource development activities at the Lahomi District Head Office, West Nias Regency. The type of research used in this research is qualitative research, with a descriptive approach. Data collection methods used include observation, interviews and documentation. Based on research findings, the results of this research indicate that training and development of human resources at the Lahomi Subdistrict Office is carried out based on an analysis of job needs and individual employees. This aims to increase employee knowledge, abilities and skills so that they can carry out their position functions and responsibilities well. Researchers provide suggestions, namely: to identify structured ones, use interview methods, surveys and open discussion forums to help understand more deeply the needs of individuals and organizations.